‘I Ain’t A-Going to Be Sivilized:’ Huck’s Idiolect in Twain’s the Adventures of Huckleberry Finn - Chaleila, Wisam Abughosh (Journal of Posthumanism, 2025)
Recent research has highlighted the significance of written dialects and idiolects in shaping literary voices, a phenomenon particularly evident in Mark Twain’s The Adventures of Huckleberry Finn (HF). This study examines Twain’s intentional use of idiolect to characterize Huck, portraying his self-made social class and nomadic lifestyle. Huck’s first-person narrative emphasizes a humanized stylistic register marked by nonstandard vernacular. Employing a deconstructionist approach, the study explores Huck’s inconsistent idiolect, linking it to themes of deterritorialization and nomadology, and positioning it as a deliberately destabilizing force within established linguistic conventions. By foregrounding Huck’s idiolect, the study contributes to broader discussions on literary representation and dialectology.